EXAMINING THE TAPI PIPELINE AND ITS IMPACT ON REGIONAL AND CROSS-REGIONAL RIVALRY - Reza FARAJI RAD, Abdol; MORADI, Heydar (CENTRAL ASIA AND THE CAUCASUS, 2012)
Before 1991, the states of Central Asia were marginal backwaters, republics of the Soviet Union that played neither a major role in the Cold War relations between the U.S.S.R. and the United States, nor in the Soviet Union’s relations with the principal regional powers of Turkey, Iran, and China. But in the 1990s, the dis-solution of the Soviet Union coincided with re-discovery of the energy resources of the Caspian Sea, attracting a wide range of international oil companies, including American majors, to the region. Eventually, the Caspian Basin became a point of tension in U.S.-Russian relations. In addition, Central Asia emerged as a zone of conflict between the regional and cross-regional powers. The events of 11 September 2001 and the terrorist groups operating in Afghanistan brought Central Asia to the forefront of U.S. attention. The growing importance of natural gas imports to to-day’s economies is compelling the world community to think anew about energy security. The pipeline from Turkmenistan to Pakistan through Afghanistan was first proposed in the mid-1990s when America’s Unocal-led energy consortium and Argentina’s Brides Company vied to sign a deal with the Taliban government in power at that time in Kabul. However, security considerations combined with international condemnation of the Taliban human rights abuses prompted both companies to pull out, leaving the project in the lurch.1 After the end of the Taliban regime, the idea was revived, and the three countries (Afghanistan, Pakistan, and Turkmenistan) signed a new agreement at the end of 2002. The Asian Development Bank (ADB) conducted a feasibility study of the project and rendered a favorable verdict in 2005. Although a framework agreement on development of the project was signed by the heads of the three governments only in December 2002,2 the Asian Development Bank remains committed to the idea of building a 1,600-km gas pipeline connecting Turkmenistan, Afghanistan, and Pakistan. In April 2008, the three countries were joined by India to implement the same expand-ed project that became known as the Turkmenistan-Afghanistan-Pakistan-India (TAPI) gas pipeline. Finally, on 11 December 2010, after nearly two years of intergovernmental deliberations, the Presidents of Turkmenistan, Afghani-stan, and Pakistan, and India’s Energy Minister signed a framework agreement at a summit in Ashghabad to build the 1,680-kilometer pipeline. It envisages constructing 1,680 km of pipeline with a total gas capacity of 90 million standard cubic meters per day (mscm/d). Some of this amount will be bought by Afghanistan. The TAPI project is expected to start in 2012 and should come on stream by 2016. The proposed pipeline will stretch from Turkmenistan’s gas fields and travel 1,680 km through Turkmenistan (145 km), Afghanistan (735 km), and Pakistan (800 km), before culminating at the Indian border town of Fazilka in Punjab.3 Annually, the pipeline will carry roughly 33 billion cubic meters of natural gas to consumers. In addition to providing clean energy, it will generate huge amounts of revenue and create employment opportunities for the people of the region. API is seen a convergence of interests, both of the great powers, as well as of the regional play-ers. The United States, for example, is propounding the project as “magic glue” that will bind the warring factions and their regional proxies into an interdependent cooperative framework. The U.S. hopes that TAPI will in all likelihood wean India away from the Iran-Pakistan-India (IPI) gas pipeline that runs from Iran’s South Pars gas complex in the Persian Gulf. In addition to further isolating Iran, the resultant interdependence and benefits of cooperation might act as a catalyst for peace between India and Pakistan.4 Geopolitics of energy will ultimately become a significant and major policy topic as the increasing competition for access to limited resources alters the global economy.